Central Asian legal system and civil society: implications of governance, social transformation, and reform - Saparbekova, E.K.; Smanova, A.B. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan are Central Asian nations that went through a crucial period of social, political, and legal change following the fall of the Soviet Union. Due to the legacy of Soviet legal systems and initiatives to fortify the legal system and foster civil society, many nations have encountered difficulties. Being an organization apart from the government, civil society has been instrumental in advancing accountability, openness, and public knowledge. Despite reform efforts, the legal system is still vulnerable to political interference and corruption. This article explores the relationship between civil society and the judicial system in Central Asia. It looks at how these components promote social justice, democracy, and the rule of law. The results indicate that although obstacles like governmental restrictions, judicial independencies, and strict regulation of non-governmental organizations still impede the advancement of this relationship, chances like global collaboration and legislative reform can open the door to change. This study uses a descriptive-analytical methodology to analyze the intricate connections between the legal system and civil society and to provide recommendations for enhancing their engagement. The study concludes that Central Asia can achieve sustainable development and rule of law by finding a balance between governmental supervision and assistance and bolstering independent, rule-of-law institutions.